EFFECTIVENESS OF TOOTHPASTE CONTAINING PROPOLIS, TEA TREE OIL, AND SODIUM MONOFLUOROPHOSPHATE AGAINST PLAQUE AND GINGIVITIS - SURIAMAH, NELLY; LESSANG, ROBERT; KEMAL, YULIANTI (International Journal of Applied Pharmaceutics, 2019)
Objective: Natural ingredients such as propolis and tea tree oil are known to possess antibacterial and anti-inflammatory effects that are effective against periodontal diseases. This study aimed to determine the effectiveness of toothpaste containing propolis, tea tree oil, and sodium monofluorophosphate against dental plaque and gingivitis. Methods: A randomized clinical trial was conducted for 7 days with 20 subjects in test (using the experimental toothpaste) and control (using toothpaste without any natural ingredients) groups each. Measurements of plaque index (PI) and papillary bleeding index (PBI) scores were performed on days 0 and 7. Results: Significant decreases (p<0.05) in PI (0.53–0.27) and PBI (0.55–0.11) scores were noted in the test group but not in the control group. Conclusions: Brushing teeth with toothpaste containing propolis, tea tree oil, and sodium monofluorophosphate might be effective in reducing the accumulation of dental plaque and the severity of gingival bleeding.